Optical characteristics of gas-discharge plasma of atmospheric pressure barrier discharge on zinc diiodide vapor with helium mixtures - Malinina, A.A.; Malinin, A.N.; Shuaibov, A.K. (Вопросы атомной науки и техники, 2018)
Investigations of the optical characteristics of a gas-discharge plasma of an atmospheric pressure barrier discharge on mixtures of zinc diiodide vapor with helium are presented. The repetition rate of the plasma pumping pulses was 130 kHz. The regularities were established: in the emission spectra of a barrier discharge plasma in the 400…750 nm range with a resolution 0.05 nm, in the temporal characteristics of voltage and current, and the radiation brightness dependences on the partial pressure of helium and nitrogen. The emission of exciplex ZnI* molecules with a maximum of intensity at λ = 602 nm, excimer molecules I₂*, and lines of zinc and helium atoms was revealed. The specific average radiation power in the spectral range Δλ = 550…650 nm was determinedwhich and it is equal to 34 mW/cm³.